@Maksudas_Id and Visual Narrative: Digital Branding Strategy in Pekanbaru - Vebby Vebby; Muammar Revnu (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study aims to analyze the visual narrative-based digital branding strategy implemented by the Instagram account @maksudas_id as a representation of creative local marketing practices in Pekanbaru. Using a qualitative case study approach, data were collected through content observation, visual element analysis, and open interviews with the account manager. The findings reveal that narrative visual strength, consistent color tones, and cultural themes are key to attracting attention and organically building brand identity. Collaboration with local communities and the use of features such as Reels and Stories also enhanced audience engagement. The study concludes that @maksudas_id successfully integrates visual elements, locality, and storytelling as an effective digital branding strategy in the age of visual marketing.